Data Analysis in Trade - R, Bhuvaneswari; M, Malathi; D, Ravi (International Research Journal of Multidisciplinary Technovation, 2019)
Data Warehousing is arisen in order to overcome the issues faced by the excel file. When several database is maintained by the excel file a conflict will arise such that which source file belongs to which excel sheet. In order to overcome the problem a data warehousing is used and a new technique used in data warehousing is soft concatenation mapping which depicts a relationship between column during transformation and concatenation .At that time many redundancy and loss of data may occur in order to overcome the issue an efficient method is used that is used to derive an approximate algorithm. This approximation is used both in real time and synthetic data sets.